1994
DOI: 10.2307/3791628
|View full text |Cite
|
Sign up to set email alerts
|

Policy Voting, Projection, and Persuasion: An Application of Balance Theory to Electoral Behavior

Abstract: In this article di$erences between rational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
12
0
3
Order By: Relevance
“…Psychological mechanisms of rationalization, such as persuasion or projection, may account for the reverse influence of voting on political values (Brody & Page, ). For example, Visser () noted that those who vote for a party for reasons other than its policies (e.g., a candidate's personality) may subsequently adapt their own positions to fit those of the party they chose. Voters may also mistakenly project their own positions on an attractive party, misperceiving its true policies.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Psychological mechanisms of rationalization, such as persuasion or projection, may account for the reverse influence of voting on political values (Brody & Page, ). For example, Visser () noted that those who vote for a party for reasons other than its policies (e.g., a candidate's personality) may subsequently adapt their own positions to fit those of the party they chose. Voters may also mistakenly project their own positions on an attractive party, misperceiving its true policies.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Several researchers have used the balance premise to understand and explain a range of attitudes and behaviors from political views, affiliations, and actions, to consumer behavior (Basil and Herr, 2006;Moore, 1978;Shaffer, 1981;Visser, 1994;Woodside and Chebat, 2001). Yet, no known study has derived hypotheses from this framework regarding peer influence on delinquency.…”
Section: Delinquent Peers and Balancementioning
confidence: 99%
“…Numerous studies (e.g., Markus & Converse, 1979;Merrill, Grofman, & Adams, 2001;Visser, 1994;Jensen, 2009) have shown that people tend to "project": They perceive parties they like as being closer to them than they actually are ("assimilation") and parties they dislike as being further away than they are ("contrast"). This may not be warranted.…”
Section: Model and Measurementmentioning
confidence: 99%